Analysing perceived role of blockchain technology in SCM context for the manufacturing industry. Issue 11 (3rd June 2021) - Karamchandani, Amit; Srivastava, Samir K.; Kumar, Sushil; Srivastava, Akhil
ABSTRACT: Blockchain is a disruptive technology that promises to embed visibility and trustworthiness in supply chains. This paper examines the perceived role of blockchain in improving SCM and profitability of organisations in the manufacturing industry. It establishes the blockchain benefits for the manufacturing industry using the process of scale development. The proposed hypotheses related to the indirect effects are based on the resource-based view of the firm. The conditional indirect effects for four organisational factors are tested. The research framework is operationalised based on data from 236 practitioners. The findings show that blockchain is perceived to drive improvement in six supply chain dimensions of the manufacturing industry. The breadth of organisation size and geographical dispersion moderate the mediation relationship between blockchain benefits and incremental profitability. Furthermore, the conditional indirect effects are found significant at mean and ±1 σ values of integration intensity and IT integration. According to managers of manufacturing industry, blockchain can bring significant improvement in delivery reliability and mass customisation, which would result in increasing the profitability of the organisation. Organisations with low integration intensity, high IT integration and small size organisations are likely to be the early adopters of blockchain technology.